1987
DOI: 10.1104/pp.83.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seed Growth in Response to Long-Term Exposures to Differing Oxygen Partial Pressures

Abstract: Short-term studies have indicated that alterations in the oxygen partial pressure (pO(2)) around developing soybean (Glycine max [L.] Merr.) seeds may alter seed growth characteristics. A 2-year field study was undertaken to determine the effects on seed development of long-term exposures of individual pods to either sub-ambient or supra-ambient pO(2). Pod chambers were used through which fixed pO(2) were continuously flowed throughout seed development. No effects on maturity date were observed from exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

1988
1988
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Quebedeaux and Hardy (12) described complete inhibition of seed set during growth at 5% 02-Subsequent experiments were conducted to explain these observations by measuring inhibition of respiration by developing seeds (5) or of phloem unloading from the seed coat (16) in short term experiments under very low 02 tensions. These explanations imply that it is the local 02 environment around the developing pod which influences seed set; however, when Sinclair et al (15) exposed developing soybean pods to 10% 02, they found only a 20% decrease in seed dry weight, compared to 81% observed by Quebedeaux and Hardy (13) when the whole aerial portion of the plant was exposed to the same regimen. These results argue that seed set is indirectly influenced by subambient 02 effects on the vegetative portion of the plant in addition to any direct inhibition of respiration and phloem unloading which may occur in the pod.…”
Section: Discussionmentioning
confidence: 91%
“…Quebedeaux and Hardy (12) described complete inhibition of seed set during growth at 5% 02-Subsequent experiments were conducted to explain these observations by measuring inhibition of respiration by developing seeds (5) or of phloem unloading from the seed coat (16) in short term experiments under very low 02 tensions. These explanations imply that it is the local 02 environment around the developing pod which influences seed set; however, when Sinclair et al (15) exposed developing soybean pods to 10% 02, they found only a 20% decrease in seed dry weight, compared to 81% observed by Quebedeaux and Hardy (13) when the whole aerial portion of the plant was exposed to the same regimen. These results argue that seed set is indirectly influenced by subambient 02 effects on the vegetative portion of the plant in addition to any direct inhibition of respiration and phloem unloading which may occur in the pod.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports document an unexpected inhibition of seed production when plants are grown at low external oxygen, with a critical oxygen pressure of around 5% (v/v) external oxygen (compared with 21% [v/v] in ambient conditions; Hardy, 1975, 1976;Sinclair et al, 1987). More detailed analyses using series of subambient oxygen tensions revealed a linear decrease in Arabidopsis seed size when external oxygen was decreased below 15% (v/v;Porterfield et al, 1999), and a progressive arrest in Arabidopsis embryo development and inhibition of protein body formation when atmospheric oxygen was decreased below 16% (Kuang et al, 1998).…”
mentioning
confidence: 99%
“…Our conclusion is not contradicted by the results of 02 enrichment studies. Testing the suffocation hypothesis, Sinclair et al (21) doubled the PO2 in the atmosphere around field grown soybean plants but found no consistent increase in seed dry weight. Effects of high PO2 have to be regarded with caution, since O2 is toxic at high PO2, due to the increased formation of free radicals (8).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that seed growth and respiration are limited by 02 diffusion into the seed (9,16,20,21). Oxygen partial pressure (kPa) high sensitivity of seed 02 uptake to PO2 in the range of 20 to 21 kPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation